Co-creation of local gastronomy for regional development in a slow city - Magnus Emmendoerfer; Thiago Chagas de Almeida; Greg Richards; Lénia Marques (Tourism & Management Studies)
This study describes the process of developing a typical dish for a slow city, using the lens of co-creation and coproduction. The slow movement argues that appreciation of local cuisine increases through events and developing slow food practices. Participant observation and interviews with actors involved in the development process revealed the symbolic components used to enhance the cultural heritage of Vizela, Portugal as a slow city. The research shows that the slow city initiative has gradually provided the basis for a gastronomic attraction to support tourist development. The development of a typical dish for the city was found to aid the recovery and revalorization of local knowledge, while the support of gastronomic culture by the local authority and community participation helped to strengthen regional identity and to develop an attractive and sustainable tourist offer. Thus, this study revealed the importance of residents in this development process as well as showed requirements that may support the rescue and cocreation of typical dishes for tourism.